Modulation of cell-cell interactions for neural tissue engineering : potential therapeutic applications of cell adhesion molecules in nerve regeneration - Chooi, Wai Hon (2019)
Neural tissue engineering holds great promise in repairing damaged nerve tissues. However, despite the promising results in regenerating the injured nervous system, tissue engineering approaches are still insufficient to result in full functional recovery in severe nerve damages. Majority of these approaches only focus on growth factors and cell-extracellular matrix (ECM) interactions. As another important component in nerve tissues, the potential of modulating cell-cell interactions as a strategy to promote regeneration has been overlooked. Within the central nervous system, there are considerably more cell-cell communications as compared to cell-ECM interactions, since the ECM only contributes 10%-20% of the total tissue volume. Therefore, modulating cell-cell interactions through cell adhesion molecules (CAMs) such as cadherins, neural cell adhesion molecules (NCAM) and L1, may be a potential alternative to improve nerve regeneration. This paper will begin by reviewing the CAMs that play important roles in neurogenic processes. Specifically, we focused on 3 areas, namely the roles of CAMs in neurite outgrowth and regeneration; remyelination; and neuronal differentiation. Following that, we will discuss existing tissue engineering approaches that utilize CAMs and biomaterials to control nerve regeneration. We will also suggest other potential methods that can deliver CAMs efficiently to injured nerve tissues. Overall, we propose that utilizing CAMs with biomaterials may be a promising therapeutic strategy for nerve regeneration.